(untitled) (Orfeu, 2023)
The book Teaching Music for People with Autism Spectrum Disorder, published in 2019, is the outcome of doctoral research led by music educator Valéria Peres Asnis, under the supervision of Professor Nassim Chamel Elias. This research was based on the project “Musicalization and socialization of children and adolescents with Autism Spectrum Disorder and their families” – carried out both at the Universidade Federal de São Carlos (UFSCar), SP, and at the Associação de Apoio e Inclusão ao Autista (AIA), in Braga, Portugal. The book is structured in three chapters through which Autism Spectrum Disorder (ASD) is presented to the reader in a didactic way, starting from a general overview about it and Applied Behavior Analysis (ABA) as a scientific basis for planning the teaching for people with autism, and arriving at the specificity of teaching music based on ABA for this population, including the provision of didactic-music activities that were prepared and adapted for this purpose.